2015
DOI: 10.3892/or.2015.3969
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of forkhead box L1 gene on osteosarcoma growth through the induction of cell cycle arrest and apoptosis

Abstract: Abstract. Forkhead box L1 (FOXL1), which is considered a novel candidate tumor suppressor, inhibits proliferation and invasion in certain types of cancer. However, the regulation and function of FOXL1 in osteosarcoma remains unclear. The expression of FOXL1 gene in osteosarcoma tissues and cell lines was examined using RT-PCR, immunohistochemistry and western blot analysis. pcDNA-FOXL1 carrying full-length FOXL1 cDNA was constructed to upregulate the level of FOXL1 expression in osteosarcoma cell lines. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…A series of novel caspase-related apoptosis-inducing pathways have been identified that may be targeted to control cancer, which have practical significance for the majority of tumors and thus, may result in breakthroughs with regard to the treatment of malignant tumors (24). The activation of caspase-9 and caspase-3 may underlie the apoptosis of fibroblasts in keloids (25). Furthermore, caspase-8 activates caspase-9 downstream of the apoptosis cascade to induce apoptosis (26).…”
Section: Discussionmentioning
confidence: 99%
“…A series of novel caspase-related apoptosis-inducing pathways have been identified that may be targeted to control cancer, which have practical significance for the majority of tumors and thus, may result in breakthroughs with regard to the treatment of malignant tumors (24). The activation of caspase-9 and caspase-3 may underlie the apoptosis of fibroblasts in keloids (25). Furthermore, caspase-8 activates caspase-9 downstream of the apoptosis cascade to induce apoptosis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that the expression of FOX genes, including FOXC2 27 , FOXF1 28 , FOXL1 29 , FOXM1 30 , 31 , FOXO1 32 , 33 and FOXP2 34 , is disrupted in osteosarcoma cells and primary tumor biopsy samples. As shown in Table 1 , according to their expression in osteosarcoma cells and primary tumor biopsy samples, these FOX genes can be divided into two groups: oncogenes and anti-oncogenes.…”
Section: Expression Of Fox Genes In Osteosarcomamentioning
confidence: 99%
“…As shown in Table 1 , according to their expression in osteosarcoma cells and primary tumor biopsy samples, these FOX genes can be divided into two groups: oncogenes and anti-oncogenes. Oncogenes primarily include FOXC2 , FOXM1 and FOXP2 , and the elevated expression level of these genes has been observed in osteosarcoma cells, which is positively correlated with tumor size, clinical stage, pathological facture, and distant metastasis 27 - 29 . Anti-oncogenes primarily include FOXF1 , FOXL1 and FOXO1 , and decreased or absent expression levels of these genes were examined in osteosarcoma cells and primary tumor biopsy samples 30 - 34 .…”
Section: Expression Of Fox Genes In Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, P21 can function as a regulator of cell cycle progression at the G1 checkpoint (15). Recently, P21 was found to be frequently downregulated in osteosarcoma, and upregulation of P21 was shown to inhibit the proliferation of osteosarcoma cells (16,17). However, the mechanisms of the regulation of P21 expression in osteosarcoma cells have remained to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%